Colossal photo-conductive gain in low temperature processed TiO2 films and their application in quantum dot solar cells - Mandal, Debranjan; Goswami, Prasenjit N.; Rath, Arup K. (Applied Physics Letters, 2017)
Colloidal quantum dot (QD) solar cells have seen remarkable progress in recent past to reach the certified efficiency of 10.6%. Anatase titanium oxide (TiO2) is a widely studied n-type widow layer for the collection of photogenerated electrons in QD solar cells. Requirement of high temperature (similar to 500 degrees C) processing steps proved to be disadvantageous for its applications in flexible solar cells and roll to roll processing, and it also has adverse commercial implications. Here, we report that solar light exposure to low temperature processed (80 degrees C-150 degrees C) TiO2 and niobium doped TiO2 films leads to unprecedented enhancement in their electron densities and electron mobilities, which enables them to be used as efficient n-type layers in quantum dot solar cells. Such photoinduced high conducting states in these films show gradual decay over hours after the light bias is taken off and can be retrieved under solar illumination. On the contrary, TiO2 films processed at 500 degrees C show marginal photo induced enhancements in their characteristics. In bilayer configuration with PbS QDs, photovoltaic devices based on low temperature processed TiO2 films show improved performance over high temperature processed TiO2 films. The stability of photovoltaic devices also improved in low temperature processed TiO2 films under ambient working conditions. Published by AIP Publishing.

Generic and scalable method for the preparation of monodispersed metal sulfide nanocrystals with tunable optical properties - Bera, Abhijit; Mandal, Debranjan; Goswami, Prasenjit N.; Rath, Arup K.; Bhagavatula L. V. Prasad (Langmuir, 2018)
A rational synthetic method that produces monodisperse and air-stable metal sulfide colloidal quantum dots (CQDs) in organic nonpolar solvents using octyl dithiocarbamic acid (C(8)DTCA) as a sulfur source, is reported. The fast decomposition of metal-C(8)DTCA complexes in presence of primary amines is exploited to achieve this purpose. This novel technique is generic and can be applied to prepare diverse CQDs, like CdS, MnS, ZnS, SnS, and In2S3, including more useful and in-demand PbS CQDs and plasmonic nanocrystals of Cu2S. Based on several control reactions, it is postulated that the reaction involves the in situ formation of a metal-C(8)DTCA complex, which then reacts in situ with oleylamine at slightly elevated temperature to decompose into metal sulfide CQDs at a controlled rate, leading to the formation of the materials with good optical characteristics. Controlled sulfur precursor's reactivity and stoichiometric reaction between C(8)DTCA and metal salts affords high conversion yield and large-scale production of monodisperse CQDs. Tunable and desired crystal size could be achieved by controlling the precursor reactivity by changing the reaction temperature and reagent ratios. Finally, the photovoltaic devices fabricated from PbS CQDs displayed a power conversion efficiency of 4.64% that is comparable with the reported values of devices prepared with PbS CQDs synthesized by the standard methods.

Improved performance and reproducibility of perovskite solar cells by jointly tuning the hole transport layer and the perovskite layer deposition - Sharma, Ashish; Rath, Arup K. (Journal of Materials Science Materials in Electronics, 2018)
Solution processed organometal trihalide materials spur tremendous attention due to their unprecedented performance in photovoltaic applications. However, submicron thick perovskite films are prone to morphological defects in the form of cracks, pinholes and porosity; the traits originated from their solution phase processing and subsequent crystallization. Moreover, pinholes and cracks in the thin film of spincoated Spiro-OMeTAD hole transport layer reduce the performance reliability by forming micro shorts and weaken the defense against moisture ingress to the perovskite layer. For the large scale processing of perovskite solar cell from the economically prudent solution phase processing, morphological shortcomings of both perovskite and hole transport layers need an urgent address. By selecting non-conventional lead precursor (lead acetate) and implementing anti-solvent treatment during film deposition, we able to form pinhole free and compact perovskite film. Crack free hole conducting layer is obtained by blending Spiro-OMeTAD with a conducting polymer without compromising in the solar cell performance. A detail investigation of the charge transport and charge extraction properties of the developed hole transport layers have been carried out. The developed CH3NH3PbI3 based perovskite solar cells show improved repeatability and performance.

Quantum dots coupled to an oriented two-dimensional crystalline matrix for solar cell application - Mandal, Debranjan; Rath, Arup K. (ACS Applied Materials & Interfaces, 2018)
Colloidal quantum dots (QDs) have emerged as promising materials to harness panchromatic solar light, owing to their size-tunable optoelectronic properties. Advancements in surface passivation strategy and processing technique have contributed immensely to their developments in photovoltaic applications. Recently, surface passivation using halometallate ligands was shown to form a protective shell layer, which reduced the structural and energetic disorder in the QD solid. Here, we report lead sulfide (PbS) QDs coupled to an oriented two-dimensionally (2D) confined crystalline matrix by using a halometallate ligand. The QDs undergo surface reconstruction during the ligand treatment process, which leads to change in their shape, size, and axis length. We show that the 2D matrix is a combination of two distinct crystalline layers consisting of a crystalline Pb amine complex and a 2D perovskite layer. The thickness of the matrix layer is modulated further by adjusting counter cations, which results in the enhancement in charge carrier mobility, carrier recombination lifetime, and diffusion length in the QD solid. 2D passivated QDs are implemented to fabricate photovoltaic devices with high power conversion efficiency of 9.1%.

Role of surface ligands in determining the electronic properties of quantum dot solids and their impact on photovoltaic figure of merits - Goswami, Prasenjit N.; Mandal, Debranjan; Rath, Arup K. (Nanoscale, 2018)
Surface chemistry plays a crucial role in determining the electronic properties of quantum dot solids and may well be the key to mitigate loss processes involved in quantum dot solar cells. Surface ligands help to maintain the shape and size of the individual dots in solid films, to preserve the clean energy band gap of the individual particles and to control charge carrier conduction across solid films, in turn regulating their performance in photovoltaic applications. In this report, we show that the changes in size, shape and functional groups of small chain organic ligands enable us to modulate mobility, dielectric constant and carrier doping density of lead sulfide quantum dot solids. Furthermore, we correlate these results with performance, stability and recombination processes in the respective photovoltaic devices. Our results highlight the critical role of surface chemistry in the electronic properties of quantum dots. The role of the size, functionality and the surface coverage of the ligands in determining charge transport properties and the stability of quantum dot solids have been discussed. Our findings, when applied in designing new ligands with higher mobility and improved passivation of quantum dot solids, can have important implications for the development of high-performance quantum dot solar cells.

Inorganic metal iodide mediated solution phase surface passivation for quantum dot solar cell - Tulsani, Srikanth Reddy; Ganguly, Saptam; Rath, Arup K. (Journal of Materials Science-Materials in Electronics, 2019)
The recent advancements in solution phase surface passivation of quantum dots (QDs) enable the development of production compatible QD ink for their large-area deposition, of a single coating. Surface passivation and colloidal stability of the QDs in polar solvents have been achieved using inorganic-organic hybrid halometallate ligands. The inorganic halometallate anions bind to the unsaturated metal sites of the QD surface, while the organic counter cations provide the colloidal stability and charge balance to the QDs. Organic ligands is a reason for concern though for the stability of the QD solar cells processed from solution-phase ligand exchange. Here, we report a solution-phase ligand exchange strategy using alkali metal halides as a substitution for the organic counterpart to facilitate solution-phase ligand exchange using all-inorganic halometallate ligands. Considering the limited solubility of the alkali halides in organic solvents a two-stage ligand-exchanged process has been commenced to help remove the excess ligands, preserve the electronic purity and allow the formation of highly passivated QD films from solution-phase deposition. A twofold increase in solar cell performance is shown with the help of the modified ligand exchange approach. The solar cell properties are further analysed through detailed characterizations of the QD solar cells.

Thiol and halometallate, mutually passivated quantum dot ink for photovoltaic application - Mandal, Debranjan; Goswami, Prasenjit N.; Rath, Arup K. (ACS Applied Materials & Interfaces, 2019)
Tunable-band-gap colloidal QDs are a potential building block to harvest the wide-energy solar spectrum. The solution-phase surface passivation with lead halide-based halometallate ligands has remarkably simplified the processing of quantum dots (QDs) and enabled the proficient use of materials for the development of solar cells. It is, however, shown that the hallometalate ligand passivated QD ink allows the formation of thick crystalline shell layer, which limits the carrier transport of the QD solids. Organic thiols have long been used to develop QD solar cells using the solid-state ligand exchange approach. However, their use is limited in solution-phase passivation due to poor dispersity of thiol-treated QDs in common solvents. In this report, a joint passivation strategy using thiol and halometallate ligand is developed to prepare the QD ink. The mutually passivated QDs show a 50% reduction in shell thickness, reduced trap density, and improved monodispersity in their solid films. These improvements lead to a 4 times increase in carrier mobility and doubling of the diffusion length, which enable the carrier extraction from a much thicker absorbing layer. The photovoltaic devices show a high efficiency of 10.3% and reduced hysteresis effect. The improvement in surface passivation leads to reduced oxygen doping and improved ambient stability of the solar cells.
Keywords: ligand; mobility; quantum dot; solar cell; surface passivation

Reduction of trap and polydispersity in mutually passivated quantum dot solar cells - Sharma, Ashish; Mahajan, Chandan; Rath, Arup K. (ACS Applied Energy Materials, 2020)
Control over surface passivation is a key to manage the optoelectronic properties in low-dimensional nanomaterials because of their high surface-to-volume ratios. Tunable band gap quantum dots (QDs) are a potential building block for the development of optoelectronic devices like solar cells, photodetectors, and light-emitting diodes. Long and insulating surface ligands of colloidally synthesized QDs are exchanged by short ligands to attain compact arrangement in thin films to facilitate the charge transport process. However, the ligand exchange process often resulted in reduced surface passivation, inhomogeneous QD fusion, and deterioration of energy band gap, which adversely impact their performance in solar cells. Here, we introduce a surface passivation strategy where the QDs are mutually passivated by the organic ligand 3-methyl mercapto propionate and inorganic halometallate ligands to develop a conducting QD ink. The mutually passivated QDs (MPQDs) show significant improvement in optoelectronic properties in maintaining the trap-free energy band gap and size monodispersity. The photovoltaic performance of MPQDs shows a 33% average increase in power conversion efficiency (PCE) over the conventional halometallate passivation to attain 9.6% PCE in MPQD solar cells. The improvements in photovoltaic parameters are corroborated by the reduction in density of the intermediate trap states and an increase in depletion width and diffusion length in MPQD-based solar cells.
Keywords: polydispersity; quantum dot; solar cells; surface passivation; trap states

Solution-phase hybrid passivation for efficient infrared-band gap quantum dot solar cells - Mahajan, Chandan; Sharma, Ashish; Rath, Arup K. (ACS Applied Materials & Interfaces, 2020)
The broad tunability of the energy band gap through size control makes colloidal quantum dots (QDs) promising for the development of photovoltaic devices. Large-size lead sulfide (PbS) QDs, exhibiting a narrow energy band gap, are particularly interesting as they can be used to augment perovskite and c-Si solar cells due to their complementary NIR absorption. However, their complex surface chemistry makes them difficult to process for the development of solar cells. The shape of the QDs transformed from octahedron to cuboctahedron as their size increases, a phenomenon guided by surface energy minimization. As a result, the surface properties change drastically for large-size QDs, which exhibit nonpolar (200) facets and polar (111) facets, as opposed to only (111) facets in small-size QDs. Recent advancements in solution-phase surface passivation strategies, used for the development of high-performance solar cells using the small size and wide band gap QDs, failed to translate a similar enhancement in the case of large-size and narrow band gap QDs. Here, we report a hybrid passivation strategy for large-size and narrow band gap QDs to passivate both (111) and (200) facets, respectively, using inorganic lead triiodide (PbI3-) and organic 3-chloro-1-propanethiol (CPT). By employing charge balance calculation, we identified the desired narrow band gap for QDs to complement the perovskite and c-Si absorption. The distinct choice of the organic ligand CPT enhances the colloidal stability of QDs in the solution phase and improves surface passivation to stop QD fusion in solid films. Photophysical properties show narrower excitonic and emission peaks and a reduction in the Stokes shift. Hybrid passivation leads to a 94% increase in the power conversion efficiency of solar cells and a 74% increase in the external quantum efficiency at the excitonic peak.
Keywords: infrared band gap; polydispersity; quantum dot; solar cells; surface passivation; trap states

Crack-free conjugated PbS quantum dot-hole transport layers for solar cells - Sharma, Ashish; Dambhare, V. Neha; Bera, Jayanta; Sahu, Satyajit; Rath, Arup K. (ACS Applied Nano Materials, 2021)
Colloidal quantum dots (QDs) benefit from solution-phase processing and band-gap tuning for their application in solar cell development. Today's QD solar cells rely on solid-state ligand exchange (SLE) to replace bulky oleic acid (OA) ligands with small 1,2-ethanedithiol (EDT) ligands to develop a conducting hole transport layer (HTL). High volume contraction in EDT conjugated QD films, however, leads to crack and porosity in the HTL, which is a major cause of concern for the device reproducibility and large-area solar cell development. We show that partial removal of the OA ligands in the solution phase reduces the volume contraction in solid films, thereby allowing the growth of crack-free QD films in the SLE process. The cleaning of QDs by repeated precipitation and redispersion using a protic methanol (MeOH) solvent helps with partial removal of the OA ligands, but it is detrimental to the electronic properties of QDs. We develop a one-step solution-phase partial ligand-exchange process using ammonium salts, which enable partial replacement of the OA ligands and passivation of the QD surface. Introduction of the facile partial ligand-exchange process eliminates the need for tedious and wasteful multiple cleaning steps with MeOH, while improving the photophysical properties of QDs. The advancement in QD processing helps to build crack-free, smooth, and conjugated QD films for their deployment as HTLs in solar cell development. Partial ligand exchange with NH4SCN leads to a 1.5 times increase in p doping and mobility over multiple MeOH-cleaned PbS QD films. HTLs developed using NH4SCN QDs show an improved photovoltaic performance to attain a 10.5% power conversion efficiency. Improvement in the depletion width and hole collection efficiency leads to a superior photovoltaic performance, as confirmed from experimental studies and one-dimensional solar cell capacitance simulation.
Keywords: Efficiency; ligand; polydispersity; quantum dot; solar cells; thin film

Perspective on perovskite solar cells - Bhaumik, Saikat; Saha, Sudip K.; Rath, Arup K. (New Research Directions in Solar Energy Technologies, 2021)

Reduction of hydroxyl traps and improved coupling for efficient and stable quantum dot solar cells - Mandal, Debranjan; Dambhare, V. Neha; Rath, Arup K. (ACS Applied Materials & Interfaces, 2021)
Progress in quantum dot (QD)-based solar cells has been underpinned by the improvements in surface passivation and advancements in device engineering. Acute control over the surface properties is crucial to restrict the formation of in-gap trap states and improve the QD coupling in achieving conducting QD films. In this report, we demonstrate a solution-phase hybrid passivation strategy, which is beneficial in removing detrimental hydroxyl traps and improving the coupling between QDs by reducing the interdot distance. Advancement in surface passivation is translated to the long carrier lifetime, higher carrier mobility, and superior protection toward degradations in QD solids. The performance of solar cell devices is increased by 26% to reach an efficiency of 10.6%, compared to the state-of-the-art lead halide passivated solar cells. The improvement in solar cell performance is supported by the reduction of trap states and an 80 nm increase in thickness of the light-absorbing QD layer.
Keywords: ligand; mobility; quantum dot; solar cell; surface passivation

Composition and surface morphology invariant high on-off ratio from an organic memristor - Betal, Atanu; Bera, Jayanta; Sharma, Ashish; Rath, Arup K.; Sahu, Satyajit (ACS Applied Electronic Materials, 2022)
Material composition plays a crucial role in the device performance; thus, nonvolatile memory devices from a small molecule named 5-mercapto-1-methyl tetrazole (MMT) in an insulating polymer matrix of poly(4-vinyl pyridine) (PVP) were fabricated. The composition of the active material in the device was varied to observe its influence on the device's electronic properties. The device with a more or less weight ratio of MMT has a much smoother surface morphology, whereas when the contributions of MMT and PVP were equal, the average surface roughness increased. However, the maximum on-off current ratio for all the devices is 10(5), suggesting that the MMT molecule does not show any change in its characteristic properties when surrounded by an insulating material. When the device was fabricated without the polymer matrix, the surface morphology of the device completely changed as it was filled with large holes. These holes provide short-circuited pathways for the current by forming the direct metal contact between the top and bottom electrodes. The carrier transport through these devices follows various conduction mechanisms. Some of the dominating conduction mechanisms are direct tunneling and trap-free and trap-assisted space-charge-limited conduction.
Keywords: Nonvolatile memory; Polymer; small molecule; space-charge; tunneling

Thiocyanate- and thiol-functionalized p-doped quantum dot colloids for the development of bulk homojunction solar cells - Dambhare, V. Neha; Sharma, Ashish; Mahajan, Chandan; Rath, Arup K. (Energy Technology, 2022)
Progress in device engineering and surface passivation strategies has led to steady progress in colloidal quantum dot (QD) solar cells. Bulk homojunction (BHJ) device architecture has several advantages over the conventional planar junction in developing QD solar cells. Herein, surface ligand chemistry is utilized to control the doping type and dispersibility of oppositely doped PbS QDs to develop BHJ solar cells. Thiocyanate and thiol ligand combination is introduced to develop p-PbS QD ink, which is blended with halide-passivated n-PbS QDs to build BHJ solar cells. It is shown that BHJ solar cells are benefited from high energy offset and higher hole mobility. This leads to the superior carrier extraction from a thicker active layer without compromising fill factor and open circuit voltage. Power conversion efficiency has reached 10.7% in 530 nm-thick BHJ solar cells, a 24% improvement over the best performing planar solar cells. With the help of the 1D solar cell capacitance simulator, it is shown that a 15% efficient QD solar cell can be realized by further improving the hole mobility above 0.1 cm(2) V-1 s(-1).
Keywords: bulk homojunctions; Doping; quantum dots; solar cells; surface functionalization

High open-circuit voltage in lead sulfide quantum dot solar cells via solution-phase ligand exchange with low electron affinity cadmium halides - Dambhare, Neha V.; Biswas, Arindam; Sharma, Anjali; Shinde, Dipak Dattatray; Mahajan, Chandan; Mitra, Anurag; Rath, Arup K. (JOURNAL OF MATERIALS CHEMISTRY A, 2023)
The deployment of colloidal quantum dots (QDs) in building high-performance solar cells and other optoelectronic applications relies on the passivation of unsaturated surface atoms through ligand engineering to attain a trap-free energy bandgap and strong QD coupling while maintaining the quantum confinement effect. Despite major advancements in surface passivation strategies, the open circuit voltage (V-oc) of lead sulfide (PbS) QD solar cells is limited by undesirable sub-bandgap states and high-bandtail states. The most advanced solution-phase ligand exchange strategy for PbS QDs depends on lead halide ligands, which improved the photocurrent and fill factor in QD solar cells significantly, but only an incremental change in V-oc is observed. Here we showcase a solution-phase hybrid ligand passivation strategy for PbS QDs using shallow electron affinity cadmium halide and thiol ligands. The cadmium halide ligand treatment results in the sub-monolayer substitution of surface Pb atoms by Cd atoms. The photophysical properties of QDs improve significantly to show intense band edge emission, diminished trap emission and reduced Urbach tail states. The photovoltaic devices built using cadmium halide-treated QDs show low reverse saturation current, which helps to attain a record 0.7 V V-oc (for a 1.28 eV bandgap) and 12.3% PCE.

Multi-bandgap quantum dots ensemble for near-infrared photovoltaics - Mahajan, Chandan; Dambhare, Neha V.; Biswas, Arindam; Sharma, Anjali; Shinde, Dipak Dattatray; Rath, Arup K. (Energy Technology, 2023)
Narrow bandgap quantum dots (QDs) are an important class of materials for near-infrared (NIR) optoelectronic devices owing to their size-tunable bandgap and chemical root processing. In photovoltaic applications, NIR QDs could be particularly useful to complement the sub-bandgap transmission loss of NIR solar radiation from perovskite and c-Si solar cells. However, insufficient carrier extraction thickness associated with the narrow NIR excitonic bandwidth of QDs limits the conversion efficacy of the broad NIR solar spectrum. Here, we utilize a multi-bandgap QD ensemble which widens the NIR absorption bandwidth to mimic the broad solar spectrum. A solution-phase ligand passivation strategy is used to control doping properties and energy level alignment of multi-bandgap QDs. We successfully developed bulk-heterojunction solar cells using the multi-bandgap QD ensemble, which yields higher carrier extraction thickness and broader NIR absorption. The gain from NIR absorption and carrier transport resulted in higher short-circuit current generation and power conversion efficiency (PCE) in solar cell devices. The champion device shows 8.73% PCE under 1.5 AM solar illumination and 7.44% and 5.05% PCE for the NIR photons transmitted from perovskite and c-Si layers.
Keywords: bulk-heterojunctions; multi-bandgap; near-infrared; quantum dots; solar cells; surface passivation

Photogating induced high sensitivity and speed from heterostructure of few-layer MoS2 and reduced graphene oxide-based photodetector - Das, Chayan; Kumar, Ashok; Kumar, Suresh; Dambhare, Neha V.; Kumar, Mahesh; Rath, Arup K.; Sahu, Satyajit (Physical Chemistry Chemical Physics, 2023)
Over the past few years, two-dimensional transition metal dichalcogenides (2D-TMDC) have attracted huge attention due to their high mobility, high absorbance, and high performance in generating excitons (electron and hole pairs). Especially, 2D molybdenum disulfide (MoS2) has been extensively used in optoelectronic and photovoltaic applications. Due to the low photo-to-dark current ratio (I-photo/dark) and low speed, pristine MoS2-based devices are unsuitable for these applications. So, they need some improvements, i.e., by adding layers or decorating with materials of complementary majority charges. In this work, we decorated pristine MoS2 with reduced graphene oxide (rGO) and got improved dark current, I-photo/dark, and response time. When we compared the performance of pristine MoS2 based device and rGO decorated MoS2 based device, the rGO/MoS2-based device showed an improved performance of responsivity of 3.36 A W-1, along with an I-photo/dark of about 154. The heterojunction device exhibited a detectivity of 4.75 x 10(12) Jones, along with a very low response time of 0.184 ms. The stability is also outstanding having the same device performance even after six months.

Ultra-fast electro-reduction and activation of graphene for high energy density wearable supercapacitor asymmetrically designed with MXene - Karim, Golam Masud; Dutta, Pronoy; Majumdar, Abhisek; Patra, Amalika; Deb, Sujit Kumar; Das, Snehasish; Dambhare, Neha V.; Rath, Arup K.; Maiti, Uday Narayan (Carbon, 2023)
Controlled perforation of graphene is vital to surpass the performance of supercapacitors that rely on their pristine form. However, their practical utilization has been halted by energy-inefficient and lengthy processing. Here, we are reporting a pulse Joule heating strategy for on-site reduction and activation to realize a multimodal porous framework made of perforated graphene using millisecond current pulses. The multimodal porosity and surface functionalities of graphene were regulated at an ultrafast rate by passing a transient current. Asdeveloped ready-to-use electrode composed of nano-to-macro multimodal porosity displays high areal capacitance of 380.2 mF cm-2 in symmetric two-electrode configuration, which is nearly 1.6 times higher than the nonelectro activated counterpart. Furthermore, a high-performance wearable asymmetric supercapacitor with an areal energy density of 107.8 mu Wh cm-2 was realized using this multimodal porous graphene in combination with suitable negative electrodes made of MXene. High energy density, together with stable and repeatable performance of the wearable device for 10000 cycles of charge-discharge and 5000 cycles of bending, signifies the importance of the as-developed device for practical wearable applications. Direct, simple processing of electrodes and orders of magnitude lower cost-and-processing-time can make the process appealing for practical wearable and other energy storage applications.
Keywords: asymmetric supercapacitor; Graphene activation; Joule heating; Solid-state supercapacitor; Wearable device

High-performance photodetector from p-n junction of vertically aligned SnS2 and reduced graphene oxide - Das, Chayan; Kumar, Suresh; Dambhare, Neha V.; Kumar, Mahesh; Rath, Arup K.; Sahu, Satyajit (ACS Applied Electronic Materials, 2024)
Semiconducting 2D transition metal dichalcogenides (TMDC) became very popular in photodetection due to their high mobility and high rate of generating electron and hole pairs. Over the past decade, MoS2 and WS2 became the most popular TMDC for several applications. On the other hand, due to the complex synthesis process compared to MoS2 and WS2, SnS2 became a less popular 2D material for photodetection. We synthesized vertically aligned SnS2 flakes by a chemical vapor deposition (CVD) process with three temperature zones with controlled argon (Ar) gas flow. Pristine SnS2-based devices are not very suitable for photodetection applications because of their low photo-to-dark current ratio (I ph /I (dark) ), high response time, and low stability. So, they need to be decorated with oppositely doped materials. We decorated pristine SnS2-based devices with rGO nanoparticles, which significantly increased the device's performance. We found a high responsivity (R) of 1.33 A/W, detectivity (D) of 6.95 x 10(11) Jones, I ph /I dark of 102, and a rise time of 0.241 ms (fall time of 1.318 ms) with the rGO decorated SnS2-based device.
Keywords: 2D-SnS2; CVD; p-njunction; photodetector; rGO

Scanning tunneling microscopy investigation of synaptic behavior in AgInS2 quantum dots: effect of ion transport in neuromorphic applications - Betal, Atanu; Chetia, Anupam; Bera, Jayanta; Saikia, Dibyajyoti; Sharma, Ashish; Rath, Arup K.; Sahu, Satyajit (ACS Applied Nano Materials, 2024)
Scanning tunneling microscopy (STM) is a powerful technique for investigating the nanoscale properties of functional materials. Additionally, scanning tunneling spectroscopy (STS) facilitates the determination of the local density of states (LDOS) within the material. In this study, we present an exploration of the resistive switching (RS) properties and neuromorphic computing capabilities of individual AgInS2 quantum dots, utilizing STM and STS techniques. By examining the material's bandgap and its temperature dependence, we uncover a nonlinear variation below the Debye temperature and a linear trend at higher temperatures. Moreover, STS measurements demonstrate changes in the conducting states induced by localized pulses, further confirming the unique characteristics of the quantum dots. The experimental devices constructed by using these quantum dots effectively replicate the RS properties observed at the nanoscale. To assess the neuromorphic application of the devices, pulse transient measurements simulating the learning and forgetting processes were conducted. The gradual set and reset processes successfully mimic the information retention and erasure capabilities essential for neuromorphic computing. Notably, the resistive switching mechanism in these devices is attributed to localized ionic transport, which highlights the significant involvement of ionic species in the observed RS behavior. The outcomes of this study contribute to the fundamental understanding of RS properties in single AgInS2 quantum dots and offer valuable insights into their potential applications in neuromorphic computing.
Keywords: corona poling; Ion transport; neuromorphic computing; quantum dots; resistive switching; Scanning tunneling microscopy; STS

Solution-phase ligand engineering for all-quantum-dot near-infrared light-emitting diodes - Biswas, Arindam; Mitra, Anurag; Sharma, Ashish; Shinde, Dipak Dattatray; Dambhare, V. Neha; Sharma, Anjali; Mahajan, Chandan; Rath, Arup K. (ACS Applied Nano Materials, 2024)
Strong emission over a wide near-infrared (NIR) region makes lead sulfide quantum dots (QDs) a preferred material in building NIR light-emitting diodes (NIR-LEDs) for numerous applications. Narrow-bandgap emitter QDs blended in the matrix of high-band gap QDs offer a simple yet powerful architectural platform for building high-performance NIR-LEDs. So far, the all-QD-based blend architecture has been realized using a poorly controlled solid-state ligand exchange approach. Advanced solution-phase ligand exchange, which offers greater control over surface passivation, is yet to be realized in all-QD LED device construction. We observe that the solution-phase ligand exchange from the optimized lead halide and thiol ligand combination, used in high-performing QD solar cell construction, is inefficient in realizing efficient all-QD LEDs, which could have restricted the adoption of the solution-phase ligand exchange thus far. Here, we introduce an innovative dual-ligand strategy to build all-QD-based NIR-LEDs using an advanced solution-phase ligand exchange approach. Through ligand engineering of matrix QDs, we managed to improve photoluminescence quantum yield (40%), reduce trap density (10(14) cm(-3)), and prolong carrier lifetime (832 ns). The LED devices benefit from improved electronic properties and balanced carrier injection to yield 6% EQE and 7.7% PCE, which are six times higher than those of state-of-the-art ligands.
Keywords: electroluminescence; lead sulfide; ligand passivation; light-emitting diodes; near-infrared; quantumdots

Synthesis and processing strategy for high-bandgap PbS quantum dots: a promising candidate for harvesting high-energy photons in solar cells - Shinde, Dipak Dattatray; Sharma, Anjali; Dambhare, Neha V.; Mahajan, Chandan; Biswas, Arindam; Mitra, Anurag; Rath, Arup K. (ACS Applied Materials & Interfaces, 2024)
The wide tunability of the energy bandgap of colloidal lead sulfide (PbS) quantum dots (QDs) has uniquely positioned them for the development of single junction and tandem solar cells. While there have been substantial advancements in moderate and narrow bandgap PbS QDs-ideal for single junction solar cells and the bottom cell in tandem solar cells, respectively; progress has been limited in high-bandgap PbS QDs that are ideally suited for the formation of the top cell in tandem solar cells. The development of appropriate high bandgap PbS QDs would be a major advancement toward realizing efficient all-QD tandem solar cells utilizing different sizes of PbS QDs. Here, we report a comprehensive approach encompassing synthetic strategy, ligand engineering, and hole transport layer (HTL) modification to implement high-bandgap PbS QDs into solar cell devices. We achieved a greater degree of size homogeneity in high-bandgap PbS QDs through the use of a growth retarding agent and a partial passivation strategy. By adjusting the ligand polarity, we successfully grow HTL over the QD film to fabricate solar cells. With the aid of an interface modifying layer, we incorporated an organic HTL for the realization of high-performance solar cells. These solar cells exhibited an impressive open-circuit voltage of 0.824 V and a power conversion efficiency of 10.7%, marking a 360% improvement over previous results.
Keywords: charge transport; lead sulfide; ligand passivation; quantum dots; solar cell

Air-stable double halide perovskite Cs2CuBiBr6: synthesis and memristor application - Betal, Atanu; Chetia, Anupam; Saikia, Dibyajyoti; Karmakar, Krishnendu; Bera, Ganesh; Dambhare, Neha V.; Rath, Arup K.; Sahu, Satyajit (Physical Chemistry Chemical Physics, 2025)
The excellent optical and electronic properties of halide perovskite materials have attracted researchers to investigate this particular field. However, the instability in ambient conditions and toxicity of materials like lead have given some setbacks to commercial use. To overcome these issues, perovskite-inspired materials with less toxic and excellent air-stable materials are being studied. Double perovskite materials are one of the perovskite materials. In this study, we have synthesized air-stable double perovskite Cs2CuBiBr6 using a solution process approach. The characterization of the material revealed that it has excellent crystallinity and high stability. The material shows excellent optical and electronic properties. It can be used in resistive memory devices. It shows stable current-voltage characteristics and analog switching. The ion migration through the active layer and accumulation of charge near the electrode region are the reasons behind the resistive switching.

Germylene mediated reductive C-C and C-N coupling of an isocyanide and its device application - Gour, Kritika; Pramanik, Debjit; Dash, Soumya Ranjan; Shinde, Dipak Dattatray; Venugopal, Geethu; Vanka, Kumar; Rath, Arup K.; Sen, Sakya S. (Angewandte Chemie-International Edition, 2025)
We have demonstrated a unique reductive coupling of 4-iodophenyl isocyanide, facilitated by a perimidine-based N-heterocyclic germylene (NHGe), which yields a bis-spirogerma compound featuring simultaneous C-C and C-N bond formation. This reaction, which leads to the oxidation of germanium from +2 to +4, represents a significant departure from previously documented isocyanide-germylene interactions. The product exhibits extensive conjugation across its bicyclic C4Ge2N2 framework, conferring distinct photophysical properties, including prominent orange luminescence in both solution and solid states. The photophysical properties are supported by the TD-DFT calculations confirming an n ->pi* transition. The potential application of this compound in optoelectronic devices, particularly as a hole transport layer in PbS quantum dot solar cells, is also explored, with promising preliminary results.
Keywords: Germylene; hole transport layer; Isocyanide; reductive coupling

Synergistic improvement of narrow bandgap PbS quantum dot solar cells through surface ligand engineering, near-infrared spectral matching, and enhanced electrode transparency - Sharma, Anjali; Shinde, Dipak Dattatray; Mahajan, Chandan; Dambhare, Neha V.; Biswas, Arindam; Mitra, Anurag; Girade, Vrushali S.; Rath, Arup K. (ACS Applied Materials & Interfaces, 2025)
The tunability of the energy bandgap in the near-infrared (NIR) range uniquely positions colloidal lead sulfide (PbS) quantum dots (QDs) as a versatile material to enhance the performance of existing perovskite and silicon solar cells in tandem architectures. The desired narrow bandgap (NBG) PbS QDs exhibit polar (111) and nonpolar (100) terminal facets, making effective surface passivation through ligand engineering highly challenging. Despite recent breakthroughs in surface ligand engineering, NBG PbS QDs suffer from uncontrolled agglomeration in solid films, leading to increased energy disorder and trap formation. The limited NIR transparency of commonly used indium-doped tin oxide (ITO) electrodes and inadequate NIR radiation from commercially available solar simulators further compromise the true performance of NBG PbS QDs in solar cells. Here, we employ a hybrid ligand strategy based on inorganic cadmium halide and organic thiol molecules, leading to the partial substitution of surface Pb atoms with Cd heteroatoms. This hybrid ligand strategy substantially reduces undesired QD fusion in solid films, improving the photophysical and electronic properties. By modulating the thickness of the ITO layer and managing refraction loss through a ZnO layer coating, we improved NIR transparency to above 80%. We combine an NIR light source with a solar simulator to achieve near-ideal spectral matching for a broader range with standard AM1.5G illumination. Enhancements in surface passivation of QDs, improvements in NIR transparency of electrodes, and a spectral matched light source setup help us achieve solar cell power conversion efficiencies of 12.4%, 4.48%, and 1.37% under AM 1.5G, perovskite filter, and silicon filter illuminations, respectively. A record open-circuit voltage (V oc) of 0.54 V and short-circuit current density (J sc) of 38.5 mA/cm2 are achieved under AM 1.5G illumination. We attribute these advancements in photovoltaic parameters to the reduction in Urbach tail states and intermediate trap density originating from superior surface passivation of QDs.
Keywords: lead sulfide; ligand passivation; near-infrared; quantum dots; solar cell; tandem solarcell

WS2 nanoparticle-decorated, vertically aligned SnS2-based high-performance heterostructures for ambient-stable ultrafast photodetection - Das, Chayan; Kumar, Suresh; Sharma, Anjali; Kumar, Mahesh; Rath, Arup K.; Sahu, Satyajit (ACS Applied Nano Materials, 2025)
The development of visible-light photodetectors with high responsivity, rapid response, and long-term ambient stability remains a critical challenge in optoelectronics. Here, we report a high-performance photodetector based on a vertically aligned SnS2 film interfaced with WS2 nanoparticles, forming a p-n heterojunction. This device is fabricated using a scalable two-step method-chemical vapor deposition (CVD) for SnS2 growth and solution-based drop-casting for WS2 deposition-enabling precise control over the heterointerface, but trap states are inevitable due to the use of thermal CVD and the drop-casting method. The resulting photodetector exhibits remarkable optoelectronic characteristics, including a responsivity of 0.76 A/W, a detectivity of 7.56 x 10(11) Jones, a photo-to-dark current ratio of 119, and a fast rise time of 0.297 ms under visible illumination. These performance metrics are directly attributed to the optimized heterointerface, where the built-in electric field at the nanoscale WS2/SnS2 junctions promotes efficient charge separation and minimizes recombination losses. Notably, the device retains over 95% of its initial performance even after 1 week of ambient exposure, highlighting its superior environmental robustness. This work introduces an interface-engineering strategy that leverages the unique electronic properties of earth-abundant, nontoxic two-dimensional materials, offering a viable pathway for scalable, high-speed, and stable photodetectors suitable for next-generation optoelectronic systems.
Keywords: 2D; CVD; heterojunction; photodetector; SnS2; WS2

Unveiling the reactivity of N-heterocyclic methylene hydrazines - Balayan, Kajal; Biswas, Arindam; Sharma, Himanshu; Tiwari, Prabhakar; Vanka, Kumar; Gonnade, Rajesh G.; Rath, Arup K.; Sen, Sakya S. (Dalton Transactions, 2026)
We present the first reactivity profile of N-heterocyclic methylene hydrazines, revealing distinct competition between steric and electronic control. Reactions with HCl are electronically driven, resulting in protonation at the proximal nitrogen, while the bulky Lewis acid B(C6F5)3 coordinates to the sterically accessible distal nitrogen. Additionally, we demonstrate that these scaffolds undergo spontaneous, base-free HCN elimination with tetracyanoethylene (TCNE) to form highly conjugated molecules with significantly reduced HOMO-LUMO gaps.